If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(m + -6) + 4 = 24 Reorder the terms: 5(-6 + m) + 4 = 24 (-6 * 5 + m * 5) + 4 = 24 (-30 + 5m) + 4 = 24 Reorder the terms: -30 + 4 + 5m = 24 Combine like terms: -30 + 4 = -26 -26 + 5m = 24 Solving -26 + 5m = 24 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '26' to each side of the equation. -26 + 26 + 5m = 24 + 26 Combine like terms: -26 + 26 = 0 0 + 5m = 24 + 26 5m = 24 + 26 Combine like terms: 24 + 26 = 50 5m = 50 Divide each side by '5'. m = 10 Simplifying m = 10
| m-2/5=3/5 | | 5f+8=-11f | | x^4+8x^3+10x^2+4=0 | | 48=3d+9 | | 562n+57n= | | -8=-3+x | | (X+3)=(x-2) | | -2(1-3a)=58 | | 2(3y+5)=-8 | | 48-3x=7x-18 | | x+yi=3+4i | | -12=-m+2 | | 3v-2(v-8)=7 | | -9x-2=7x-2.2 | | (2x+1)=(3x+2) | | 5(4x+1)=2x-8x | | 5h=-65 | | 8a-29=51 | | 5h=-96 | | 6(9+3x)=126 | | 7w=-1 | | (X+3)=(2x+4) | | 15x-9=10x-14 | | 5=h-(-2) | | (X^5)+(5X^4)-(2X^3)-(10X^2)+(X)+5=0 | | 3v-4=-10 | | (x+1)=(x+2) | | 5n-2=20 | | x(x+1)=118 | | 4x-3=122 | | 69-3X=6X+23 | | 288=x(x(4.5)) |